2023
DOI: 10.1093/tas/txad001
|View full text |Cite
|
Sign up to set email alerts
|

An immersive field trip focused on beef production increases the sense of belonging in ethnoracial minority college students

Abstract: Sense of belonging is a student’s sense of feeling accepted, valued, and included by others in their discipline. Imposter syndrome is self-perceived intellectual fraud in areas of success. Sense of belonging and imposter syndrome can influence behavior and well-being and are linked to academic and career outcomes. Our objective was to evaluate if a five-day tour of the beef cattle industry changed college students’ sense of belonging and imposter tendencies with a focus on ethnicity/race. Procedures involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is important to note, however, that not all students consented to participate in the current study which could have introduced a potential source of bias into the results (e.g., those that did not feel like they belonged or had more negative perceptions of agriculture may not have participated). Other studies have found that race and gender, and the unbalanced representation of minority demographic groups, can impact the sense of belonging in STEM majors (Rainey et al, 2018;Sax et al, 2018;Mooney and Becker, 2020;Drewery et al, 2023); for example, compared to their white counterparts, ethnoracial minority students enrolled in an agricultural major were less likely to report that they belonged in agriculture (Drewery et al, 2023). In regard to perceptions about food production, much of the past research focuses on how consumer demographics, such as age, gender, and household income, relate to food purchase decisions, preferences for, perceptions of, and willingness to pay for livestock and poultry (Prickett et al, 2010;Bejaei et al, 2011;McKendree et al, 2014;Miranda-de la Lama et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that not all students consented to participate in the current study which could have introduced a potential source of bias into the results (e.g., those that did not feel like they belonged or had more negative perceptions of agriculture may not have participated). Other studies have found that race and gender, and the unbalanced representation of minority demographic groups, can impact the sense of belonging in STEM majors (Rainey et al, 2018;Sax et al, 2018;Mooney and Becker, 2020;Drewery et al, 2023); for example, compared to their white counterparts, ethnoracial minority students enrolled in an agricultural major were less likely to report that they belonged in agriculture (Drewery et al, 2023). In regard to perceptions about food production, much of the past research focuses on how consumer demographics, such as age, gender, and household income, relate to food purchase decisions, preferences for, perceptions of, and willingness to pay for livestock and poultry (Prickett et al, 2010;Bejaei et al, 2011;McKendree et al, 2014;Miranda-de la Lama et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There are also opportunities to interact with students outside of the classroom (i.e., during office hours or before or after class) who have identified feeling as though they do not fit in or maybe have limited participation in class to help promote a sense of belonging. A novel teaching opportunity, i.e., an immersive field trip of the beef cattle industry in the Texas panhandle, improved minority students' sense of belonging in the agricultural field (Drewery et al, 2023), which is a promising teaching tool for improving sense of belonging among animal science students, particularly among minority students in agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the learning process must be developed in an appropriate way so that students get, manage, use and communicate what they have obtained in the learning process (Mandasari et al, 2021;Rahmah et al, 2023). One method that can be used to determine the quality of the teaching process is through the field trip method (Drewery et al, 2023;Higgins et al, 2012;Julien & Chalmeau, 2022;Santos, 2023). Learning activities in this method are not just playing to refresh the mind and cure boredom, but rather to educate students and make them understand subjects well, so that material can be conveyed to students properly (Malik et al, 2022).…”
Section: Introductionmentioning
confidence: 99%